Neuroprotective effect of Citrus limon juice against scopolamine induced amnesia in Wistar rats: Role of cholinergic neurotransmission monitoring and beta-actin signaling - Yogesh Chand Yadav; Amita Singh; Sanjay K Kannaujia; Ramakant Yadav (Elsevier, 2022)
Lemon (Citrus limon) Rutaceae) is one of the most popular world fruit crops, contains active phytochemicals that are polyphenolic compounds, flavonoids, vitamin C, folic acid, potassium, pectin etc. The bioactives compound of lemon are preventing radical-mediated diseases like cancer, diabetes, neurodegenerative disorders but no one reported that effect of Citrus limon juice on scopolamine induced amnesia model in animal. Rats were divided into five groups. Group 1 rats (normal control) received 1 ml/kg normal saline for 14 days intraperitoneally (i.p.). Group 2 rats received scopolamine (3 mg/kg, i.p.) 30 min prior to the trial on the 14th day. Group 3 rats received 3 mg/kg/day of donepezil as pre-treatment for 14 days and scopolamine (3 mg/kg, i.p.) 30 min prior to the trial on the 14th day. Group 4 and 5 rats received Citrus limon juice (0.6, 1.2 ml/kg/day) for 14 days and scopolamine (3 mg/kg, i.p) 30 min prior to the trial on 14th day respectively. On the day 14, working memory and long-term memory in rats were tested by experimental paradigms and Morris Water Maze (MWM) task. On day 15, 6 rats of each group were sacrificed and brain tissue of these rats was isolated for the estimation of biochemical parameters, histopathological examination and western blot analysis. Scopolamine treated rats showed significantly increased escape latency (p<0.0001), Acetylcholinesterase (AchE) activity (P < 0.001), lipid peroxidation (p<0.001) and significantly decreased GSH level (p< 0.001) in the hippocampus compared to the control group. These parameters were significantly recovered in the rats pretreated with Citrus limon juice and donepezil. Histopathological examination showed that Citrus limon juice and donepezil provided significant protection against pyramidal cell degeneration, neuronophagia, and thickened endothelium of blood vessels with perivascular and moderately inflammatory cells like eosinophils in scopolamine treated rats. Furthermore, Citrus limon juice was found to significantly upregulate the expression levels of ERK and beta-actin proteins in rat hippocampus. The findings of this study demonstrated that Citrus limon juice and their constituents have potential to improve the cognitive performance in scopolamine induced amnesia in Wistar rats. Further extensive studies are needed to explore the efficacy of Citrus limon juice and its constituents for treatment of various neurodegenerative diseases such as Alzheimer's disease.